THE STUDY OF KARST DESERTIFICATION MAROS PANGKEP BASED ON LANDSAT 8 OLI IMAGERY - Eko Budiyanto; Nugroho Hari Purnomo; Muzayanah Muzayanah; Aida Kurniawati; Ketut Prasetyo; Nastiti Sigra Dewi Maginta (Universitas Sebelas Maret (UNS), 2022)
This study aimed to examine the spectral imagery of Landsat 8 OLI that can determine the level of tropical karst desertification Maros Pangkep South Sulawesi. The study method is based on the characteristics of spectral imagery of Landsat 8 OLI. Spectral characteristic analysis was conducted based on derivative index values of Landsat 8 OLI of single-channel spectral values, index spectral values, maximum values, mean, minimal index, and spatial analysis. The results showed that spectral imagery of Landsat 8 OLI can be used as the identifier of the desertification process, that is in band 5 whose maximum value is indicated by the spectral value of vegetation. The karst desertification level in the study area showed that 0.3% of the regions were strongly desertified or 0,97 km2 , 4.1% of medium desertified or 12,03 km2, 16.7% were mildly desertified or 49,17 km2, and 78.9% were not desertified or 232,57 km2. Observation results for image accuracy shows that strongly desertified areas of land use are mining and cement industries, the medium desertified areas are utilized for marble mining, the mildly desertified areas are utilized for agricultural land, and not desertified areas land are being utilized for tropical rain forest is still dense.